Serial evaluation of thoracic radiographs and acute phase proteins in dogs with pneumonia. (26th May 2022) - Menard, Julie; Porter, Ian; Lerer, Assaf; Robbins, Sarah; Johnson, Philippa J.; Goggs, Robert
Abstract: Background: Acute phase proteins (APP) may guide treatment of pneumonia in dogs but correlations with radiographic abnormalities are poorly characterized. Objectives: Develop a thoracic radiographic severity scoring system (TRSS), assess correlation of radiographic changes with APP concentrations, and compare time to APP and radiograph normalization with duration of antimicrobials treatment. Animals: Sixteen client‐owned dogs, 12 with aspiration pneumonia, and 4 with community‐acquired pneumonia. Methods: Concentrations of C‐reactive protein (CRP), serum amyloid A (SAA), and haptoglobin were measured on days 1, 3, 7, 14, 28, and 60 and orthogonal 2‐view thoracic radiographs were obtained on days 1, 7, 14, 28, and 60. Treatment was clinician‐guided and blinded to APP concentrations. Radiographic severity scores were assigned by blinded, randomized retrospective review by 2 board‐certified radiologists with arbitration by a third radiologist. Results: Median (interquartile range [IQR]) time to normalization of CRP (7 days [7‐14]) and SAA concentrations (7 days [7‐14]) were shorter than antimicrobial treatment duration (17.5 days [14.5‐33.5]; P = .001 and .002, respectively) and TRSS normalization (14 days [8.8‐52], P = .02 and .02, respectively). The CRP and SAA concentrations were positively correlated with TRSS (CRP r s, 0.643; SAA r s, 0.634; both P < .0001). Both CRP and SAA identified normal thoracic radiographs area under the curve (AUC) 0.873 and 0.817, respectively, both P < .0001. Interobserver agreement for TRSS assignment was moderate ( κ, .499; P < .0001). Conclusion and Clinical Importance: Concentrations of CRP and SAA normalized before radiographic resolution and before clinicians discontinued antimicrobial treatment. The CRP and SAA concentrations may guide duration of antimicrobial treatment for dogs with pneumonia.